Influence of Tempering on Mechanical Properties of Ferrite and Martensite Dual Phase Steel. (2015) - Li, H.; Gao, S.; Tian, Y.; Terada, D.; Shibata, A.; Tsuji, N.
Abstract: This study investigated the change in microstructure and mechanical properties by tempering a low carbon dual phase steel composed of ferrite and martensite. The microstructure analysis revealed that tempering process resulted in the carbide precipitation and coarsening of martensite structures. The nanohardness of each phase (martensite and ferrite) decreased with increasing the tempering temperature. The ultimate tensile strength had a linear relationship with nanohardness ratio of martensite and ferrite. On the other hand, the uniform elongation firstly did not change by tempering at the temperature below 400 °C, but then decreased by tempering at the temperature above 400 °C with decreasing the nanohardness ratio. It was concluded that the nanohardness ratio can be a good parameter for controlling the mechanical properties of dual phase steels.